1988
DOI: 10.1128/aem.54.10.2354-2360.1988
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Conversion of α-Ionone, α-Methylionone, and α-Isomethylionone

Abstract: a-Ionone, a-methylionone, and a-isomethylionone were converted by Aspergillus niger JTS 191. The individual bioconversion products from a-ionone were isolated and identified by spectrometry and organic synthesis. The major products were cis-3-hydroxy-a-ionone, trans-3-hydroxy-a-ionone, and 3-oxo-a-ionone. 2,3-Dehydro-a-ionone, 3,4-dehydro-o-ionone, and 1-(6,6-dimethyl-2-methylene-3-cyclohexenyl)-buten-3-one were also identified. Analogous bioconversion products from a-methylionone and a-isomethylionone were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…When starting from racemic ␣-ionone [(6R)-(Ϫ)/(6S)-(ϩ)], one would expect to find the four diastereoisomers of the hydroxy product (Fig. 2) in equal amounts if hydroxylation was not stereoselective, as reported, e.g., for A. niger JTS 191 (18). In the chiral-phase gas chromatograms, though, only two major product peaks appear, representing the two enantiomers (3R,6R)-and (3S,6S)hydroxy-␣-ionone (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…When starting from racemic ␣-ionone [(6R)-(Ϫ)/(6S)-(ϩ)], one would expect to find the four diastereoisomers of the hydroxy product (Fig. 2) in equal amounts if hydroxylation was not stereoselective, as reported, e.g., for A. niger JTS 191 (18). In the chiral-phase gas chromatograms, though, only two major product peaks appear, representing the two enantiomers (3R,6R)-and (3S,6S)hydroxy-␣-ionone (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…c The two values are the value from the ␤-ionone experiment before the slash and the value from the ␣-ionone experiment after the slash. hydroxy derivative, not to a product mixture as, e.g., A. niger does (18). A detailed 1 H NMR analysis (see below) shows this in fact to be 3-hydroxy-␣-ionone.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The microbial biotransformation of racemic α‐ionone using different Streptomyces strains,19 fungi such as Aspergillus niger, 20 immobilized cells of Nicotium tabacum, 21 and cultured cells of Caragana chamlagu 22 has been reported. Moreover, different bacterial P450s from Bacillus subtillus, Sorangium cellulosum, Novaspinghobium aromaticivorans and Streptomyces have been shown to hydroxylate α‐ionone 2327.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in these study the attractiveness of IN is higher than SP which opposed the previous studies these activity in the laboratory that gave moderate attractiveness that the mixture of isophorol and isophorone is higher than the mixture of -ionol and ionone. The previous study reported α-ionol and α-ionone and their derivatives could be attracted Bactrocera latifrons [5], especially 3-oxo-ionone and 3-oxo-ionol that were synthesized from microbial conversion could be attract higher than α-ionone and α-ionol [11]. Although, these attractants, α-ionone and α-ionol could be attracted fairly otherwise it response for these attractant with short time [12].…”
Section: Resultsmentioning
confidence: 99%